Strategi Pendidikan dalam Al-Qur’an: Kajian Tafsir Tarbawi tentang Keteladanan, Nasihat, Dialog, dan Kisah - Endi Suhendi; Badruzzaman M. Yunus; Asdianur Hadi; A. Baijuri (Lembaga Pengembangan Kinerja Dosen, 2026)
A mid the growing complexity of contemporary education, the challenge of integrating intellectual achievement with moral and spiritual development has become increasingly urgent. This study examines educational strategies in the Qur’an through the perspective of tafsir tarbawi, focusing on four core approaches: exemplary conduct, advice, dialogue, and storytelling. The research aims to explore how the Qur’an presents pedagogical methods that not only convey knowledge but also shape character and internalize values in learners. Employing a qualitative library research design with thematic and tafsir tarbawi approaches, this study analyzes relevant Qur’anic verses and supporting scholarly literature. The findings reveal that the Qur’an offers a holistic and dynamic model of education in which exemplary conduct functions as a behavioral model, advice serves as a means of value internalization, dialogue promotes reflective and critical thinking, and storytelling strengthens moral awareness through narrative experience. These strategies are interconnected and operate across cognitive, affective, and behavioral domains. The study concludes that Qur’anic educational strategies remain highly relevant for contemporary Islamic education, particularly in strengthening character formation, reflective learning, and the integration of values in educational practice.